MiR-146a Restoration Suppresses Triple-Negative Breast Cancer Cell Migration: A Bioinformatic and In Vitro Study - Leila Tebbi; Behzad Mansoori; Sahar Safaei; Shahriar Hashemzadeh; Masoud Shirmohamadi; Khalil Hajiasgharzadeh; Mahdi Abdoli Shadbad; Behzad Baradaran (Tabriz University of Medical Sciences, 2022)
Purpose: Breast cancer is one of the most commonly diagnosed types of cancer worldwide. Thiscancer is treated with various methods like mastectomy, chemotherapy, hormone therapy, andradiotherapy. Among them, targeted therapy, like microRNA (miRNA) replacement therapy, isconsidered a new approach to treating breast cancer.Methods: Data analysis from TCGA datasets were used to investigate the expression of hsamiR-146a-5p in breast cancer. MTT assay was used to evaluate the viability of MDA-MB-231cells after hsa-miR-146a-5p ectopic expression. A wound-healing assay was used to observemigration in the MDA-MB-231 cell line and the effect of the hsa-miR-146a-5p ectopic expressionon migration. Finally, quantitative reverse transcription polymerase chain reaction (qRT-PCR)was used as a method to determine the effect of the hsa-miR-146a-5p ectopic expression onthe expression of CXCR4, β-catenin, MMP2, MMP9, and Vimentin genes known to be involvedin invasion and migration of MDA-MB-231 cells.Results: Our results indicated that hsa-miR-146a-5p is not involved in apoptosis in the MDAMB-231 cells, while it is highly effective in migration inhibition. MMP9, MMP2, CXCR4, andVimentin expressions were suppressed by hsa-miR-146a-5p induction; however, it induced theexpression of β-catenin.Conclusion: Some non-coding RNAs, such as hsa-miR-146a-5p, are effective in breast cancertargeted therapy. As cancer is a complicated disorder, therefore the combination of therapiesmight lead to novel therapeutic strategies.